Diaphragm, battery cell, battery, and energy storage device or system

CN122992285APending Publication Date: 2026-10-27HEFEI HONGCHU TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611114670.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]目前,针对大容量、高体积能量密度储能电芯,能够主动、可控触发安全保护的方案较少,现有方式多依靠缺陷诱发失控,会损害电芯本征安全,难以满足大容量储能电芯的安全需求

Benefits of technology

[0025]在本申请的第三方面,本申请提出了一种电池。根据本申请的实施例,所述电池包括第二方面所述的电芯。由于本申请的电池采用搭载温度敏感型隔膜的储能电芯,电芯可在异常过充时主动可控收缩、提前触发微短路终止充电,抑制单电芯热失控蔓延,从源头降低整串、整组电池发生连锁热失控和爆燃的风险,大幅提升电池系统整体安全冗余。本领域技术人员能够理解,该电池具备前述隔膜和电芯的所有优点,此处不再一一赘述。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992285A_ABST
    Figure CN122992285A_ABST
Patent Text Reader

Abstract

The application discloses a diaphragm, an electric core, a battery and an energy storage device or system, wherein the sensitive coefficient Ts of the diaphragm satisfies: Ts≥1.8 at 120 DEG C; Ts<1.8 at 140 DEG C; wherein Ts=(MD direction tensile strength+TD direction tensile strength)×10 ‑5 / thermal shrinkage; the sum of the MD direction tensile strength and the TD direction tensile strength of the diaphragm is greater than or equal to 5400 kgf / cm 2 The diaphragm of the application can guarantee the dimensional stability and intrinsic safety of the electric core at a normal use temperature of 120 DEG C, and can greatly shrink at an abnormal overcharge high temperature of 140 DEG C, actively triggers internal short circuit of the electric core, forcibly terminates continuous charging, and can avoid explosion and blasting caused by excessive energy accumulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, specifically to a separator, a cell, a battery, and an energy storage device or energy storage system. Background Technology

[0002] With the increasing development of large-capacity energy storage cells, cell capacity and size are constantly increasing, but this also brings about the deterioration of thermal safety, including thermal runaway.

[0003] Lithium iron phosphate (LFP) cells typically consist of a positive electrode, a negative electrode, and a separator between the electrodes. The separator provides electronic insulation and ion conduction. In actual use, if abnormal charging occurs within the cell and cannot be stopped in time, the internal temperature of the battery will continue to rise. The separator will shrink and melt due to heat, leading to direct contact between the positive and negative electrodes, creating a short circuit. This triggers a chain reaction within the battery and rapidly causes overall thermal runaway. The larger the cell capacity and the higher the volumetric energy density, the more energy accumulates during abnormal charging, drastically increasing the risk of cell explosion and seriously threatening the safety of the cell and the entire battery module.

[0004] Currently, there are few solutions for actively and controllably triggering safety protection for large-capacity, high-volume-energy-density energy storage cells. Existing methods mostly rely on defects to induce runaway, which will damage the intrinsic safety of the cell and make it difficult to meet the safety requirements of large-capacity energy storage cells. Summary of the Invention

[0005] This application aims to at least partially address one of the technical problems in related technologies. To this end, this application provides a separator with a specific temperature sensitivity coefficient Ts for high-capacity, high-volume-energy-density energy storage cells. This separator ensures the dimensional stability and intrinsic safety of the cell during normal operation at a normal operating temperature of 120°C; under abnormal overcharge conditions at 140°C, it can undergo significant and drastic contraction, actively triggering an internal short circuit within the cell, forcibly terminating continuous charging, and preventing deflagration or explosion due to excessive energy accumulation. This application, through the aforementioned temperature-sensitive separator, utilizes the correlation between the separator's tensile strength and thermal shrinkage to achieve intrinsic safety assurance for the cell during normal use, as well as active safety protection under abnormal operating conditions.

[0006] Therefore, in a first aspect of this application, a diaphragm is proposed. According to an embodiment of this application, the sensitivity coefficient Ts of the diaphragm satisfies: at 120°C, Ts ≥ 1.8; at 140°C, Ts < 1.8; where Ts = (tensile strength in the MD direction + tensile strength in the TD direction) × 10 -5 / Heat shrinkage rate; The sum of the tensile strength in the MD direction and the tensile strength in the TD direction of the diaphragm is ≥5400 kgf / cm 2 .

[0007] This application limits the sum of the tensile strengths of the diaphragm in the MD and TD directions to no less than 5400 kgf / cm² (i.e., the tensile strength in at least one of the MD and TD directions is no less than 2700 kgf / cm²). This causes the diaphragm to form a highly oriented structure in this high tensile strength direction due to the large stretching ratio, thereby increasing the proportion of extended crystal chains inside the diaphragm. The higher the proportion of extended crystal chains in the diaphragm, the greater the shrinkage of the base film when heated to the initial melting point. Based on this intrinsic relationship, the inventors constructed a quantitative relationship for the sensitivity coefficient Ts, where Ts = (tensile strength in the MD direction + tensile strength in the TD direction) × 10 -5 / Thermal shrinkage rate. Under normal operating temperature of 120℃, the membrane molecular chain structure is stable, and the thermal shrinkage rate is effectively suppressed, resulting in Ts≥1.8. The membrane size deformation is minimal, maintaining insulation and isolation between the positive and negative electrodes and normal ion conduction, ensuring the intrinsic safety of the cell under normal operating conditions. When the cell is abnormally overcharged and the temperature rises to 140℃, the high proportion of straightened crystal chains in the membrane relaxes and rebounds, leading to a significant increase in thermal shrinkage, resulting in Ts<1.8. At this time, the membrane actively shrinks significantly, causing a micro-short circuit to form between the positive and negative electrodes, thereby dissipating excess power in time, terminating continuous charging, and avoiding excessive energy accumulation that could induce chain side reactions and thermal runaway explosion. In summary, this application achieves the dual effect of membrane safety at low temperatures and active shrinkage protection at high temperatures through quantitative matching of tensile strength and sensitivity coefficient Ts. It eliminates the need for additional defect-inducing structures, making the design simple and controllable. It is suitable for large-capacity, high-volume energy-density energy storage cells, effectively reducing the risk of thermal runaway and explosion, and improving the overall safety of the cell and module.

[0008] In some embodiments, the thermal shrinkage rate of the diaphragm at 120°C and after standing for 1 hour is no greater than 3%.

[0009] In some embodiments, the diaphragm has a heat shrinkage rate of 6% to 50% under conditions of standing at 140°C for 1 hour.

[0010] In some implementations, Ts is 1.8 to 100 at 120°C.

[0011] In some implementations, Ts is 0.1 to 1.7 at 140°C.

[0012] In some embodiments, the diaphragm has a heat shrinkage rate of 1% to 3% under conditions of standing at 120°C for 1 hour.

[0013] In some embodiments, the diaphragm has a thermal shrinkage rate of 6% to 30% under conditions of standing at 140°C for 1 hour.

[0014] In some embodiments, the diaphragm includes a base membrane having an inorganic coating on at least one side surface.

[0015] In some embodiments, the tensile strength of the diaphragm is related to the diaphragm thickness based on the thickness of the base film.

[0016] In some embodiments, the base film is selected from polyolefin films.

[0017] In some embodiments, the polyolefin film is selected from any one of polypropylene film, polyethylene film, or composite film of polypropylene and polyethylene.

[0018] In some embodiments, the thickness of the base film is ≥3 μm.

[0019] In some embodiments, the porosity of the base membrane is 25% to 45%.

[0020] In some embodiments, the inorganic coating is made of alumina or boehmite.

[0021] In some embodiments, the thickness of the inorganic coating is ≤4μm.

[0022] In some embodiments, the surface of the inorganic coating is provided with an adhesive.

[0023] In a second aspect, this application proposes a battery cell. According to an embodiment of this application, the battery cell includes one or more electrode cores, at least one of which includes the separator described in the first aspect. Because this battery cell uses the aforementioned separator with a specific temperature sensitivity coefficient Ts, it possesses all the structural features and technical advantages corresponding to that separator, effectively suppressing the spread of internal chain side reactions and significantly reducing the probability of overcharging, thermal runaway, and deflagration in high-capacity, high-volume-energy-density battery cells. Those skilled in the art will understand that this battery cell possesses all the advantages of the aforementioned separator, which will not be elaborated upon here.

[0024] In some embodiments, the cell includes multiple electrodes, and the separators of at least two electrodes have different Ts values ​​at 140°C.

[0025] In a third aspect, this application proposes a battery. According to an embodiment of this application, the battery includes the cell described in the second aspect. Because the battery of this application uses an energy storage cell equipped with a temperature-sensitive separator, the cell can actively and controllably shrink during abnormal overcharging, prematurely triggering a micro-short circuit to terminate charging, suppressing the spread of thermal runaway from a single cell, and reducing the risk of cascading thermal runaway and explosion of the entire string or battery pack from the source, significantly improving the overall safety redundancy of the battery system. Those skilled in the art will understand that this battery possesses all the advantages of the aforementioned separator and cell, which will not be elaborated upon here.

[0026] In a fourth aspect, this application proposes an energy storage device or system. According to embodiments of this application, the energy storage device or system includes the battery described in the third aspect. Therefore, the energy storage device or system of this application, equipped with a battery using the cells of this application, can significantly reduce the risk of cascading thermal runaway, fire, and explosion in the energy storage device, battery cluster, and even the entire energy storage system, thereby improving the overall system operational safety. Those skilled in the art will understand that this energy storage device or system possesses all the structural features and technical advantages of the aforementioned separator, cell, and battery, which will not be elaborated upon here.

[0027] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0028] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 The diagram shows the shrinkage results of the diaphragms of Example 1 and Comparative Example 1 after standing at 140°C for 1 hour (where diaphragm 1-1 and diaphragm 1-2 are the results of the diaphragm of Example 1 before and after heat shrinkage, respectively, and diaphragm 2-1 and 2-2 are the results of the diaphragm of Comparative Example 1 before and after heat shrinkage, respectively). Figure 2 This is a comparison chart of the total charging energy of the battery cells of Embodiment 1 and Comparative Example 1 according to this application (Separator 1 represents the separator of Embodiment 1, and separator 2 represents the separator of Comparative Example 1). Figure 3 The AB bipolar core diaphragm design according to the embodiments of this application is used, where diaphragm a is a specific temperature-sensitive diaphragm. Detailed Implementation

[0029] The embodiments of this application are described in detail below. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application.

[0030] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Furthermore, in the description of this application, unless otherwise stated, "multiple" means two or more.

[0031] The endpoints and any values ​​of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this application.

[0032] In this application, the terms "comprising" or "including" are open-ended expressions, meaning they include the content specified in this application but do not exclude other aspects.

[0033] In this application, the term "MD direction" refers to the longitudinal / machine direction, which is the longitudinal direction of the machine along the equipment during the diaphragm production process, where the membrane is continuously stretched and extended. The term "TD direction" refers to the transverse / width direction, which is the transverse direction of the diaphragm that is perpendicular to the MD longitudinal direction and distributed along the width of the diaphragm.

[0034] In this application, the term "core" refers to an independent electrochemical basic unit inside the battery cell, which is the smallest stacked / wound electrochemical combination unit formed by assembling positive electrode plates, negative electrode plates, and separators through stacking or winding. The core does not contain a shell, electrolyte, or encapsulation structure and is the core internal component that constitutes the battery cell.

[0035] In this application, the term "cell" refers to the smallest independent electrochemical energy storage unit formed by placing one or more of the aforementioned electrode cores into a casing and then subjecting it to vacuum baking, electrolyte injection, sealing, formation, and aging. A cell includes an electrode core, electrolyte, casing, and sealing structure, and has independent charging and discharging capabilities, serving as the basic unit for forming a single battery cell.

[0036] In this application, the term "battery" refers to a single finished device that can be directly put into use after being formed by packaging, matching accessories, and series and parallel integration of one or more cells; it can also refer to a battery module composed of multiple cells / single batteries, which is suitable for the whole machine application scenarios of energy storage devices and energy storage systems.

[0037] In this application, the term "extreme operating conditions" refers to a cell or battery being subjected to harsh operating, environmental, or abuse conditions beyond its standard design tolerance range, which can easily lead to safety risks such as thermal runaway, bulging, fire, and explosion. For example, extreme operating conditions include extreme high and low temperature environments, alternating high and low temperature environments, high humidity and heat environments, high-rate charging and discharging, overcharging and over-discharging, mechanical compression, impact, puncture, as well as various unconventional and harsh usage scenarios such as heavy vehicle loads and extreme power output.

[0038] As the energy storage industry rapidly develops towards larger capacity and higher volumetric energy density, the capacity and size of energy storage cells are constantly increasing, providing more efficient energy storage solutions for scenarios such as large-scale energy storage power stations, industrial and commercial energy storage, and grid peak shaving. However, at the same time, the increase in cell capacity and volumetric energy density has also brought about significant deterioration in thermal safety performance, among which the risk of thermal runaway caused by overcharging is particularly prominent, seriously restricting the large-scale application of large-capacity, high-volume-energy-density energy storage technology.

[0039] Currently, there is a lack of active safety protection solutions for large-capacity, high-volume-density energy storage cells. Existing technologies mostly rely on defect-related methods to trigger cell runaway. These methods compromise the intrinsic safety of the cell and cannot achieve controllable, stable, and active safety protection, making them unsuitable for the application requirements of large-capacity, high-volume-density energy storage cells. Furthermore, existing separators primarily focus on passively preventing shrinkage to avoid short circuits, lacking active protection mechanisms for overcharge conditions. This fails to stop the thermal runaway chain reaction caused by overcharging at its source, making it difficult to meet the stringent safety requirements of large-capacity energy storage systems. Therefore, developing a technical solution that can achieve active safety protection and is compatible with large-capacity, high-volume-density energy storage cells has become an urgent technical problem to be solved in this field.

[0040] Therefore, in a first aspect of this application, a diaphragm is proposed. According to an embodiment of this application, the sensitivity coefficient Ts of the diaphragm satisfies: at 120°C, Ts ≥ 1.8; at 140°C, Ts < 1.8; where Ts = (tensile strength in the MD direction + tensile strength in the TD direction) × 10 -5 / Heat shrinkage rate; The sum of the tensile strength in the MD direction and the tensile strength in the TD direction of the diaphragm is ≥5400 kgf / cm 2 .

[0041] This application limits the sum of the tensile strengths of the diaphragm in the MD and TD directions to no less than 5400 kgf / cm² (i.e., the tensile strength in at least one of the MD and TD directions is no less than 2700 kgf / cm²). This causes the diaphragm to form a highly oriented structure in this high tensile strength direction due to the large stretching ratio, thereby increasing the proportion of extended crystal chains inside the diaphragm. The higher the proportion of extended crystal chains in the diaphragm, the greater the shrinkage of the base film when heated to the initial melting point. Based on this intrinsic relationship, the inventors constructed a quantitative relationship for the sensitivity coefficient Ts, where Ts = (tensile strength in the MD direction + tensile strength in the TD direction) × 10 -5 / Thermal shrinkage rate. Under normal operating temperature of 120℃, the molecular chain structure of the separator is stable, and the thermal shrinkage rate is effectively suppressed, resulting in Ts≥1.8. The size deformation of the separator is minimal, which can maintain the insulation and isolation between the positive and negative electrodes and the normal conduction of ions, ensuring the intrinsic safety of the cell under normal operating conditions. When the cell is abnormally overcharged and the temperature rises to 140℃, the high proportion of straightened crystal chains in the separator relaxes and rebounds, resulting in a significant increase in thermal shrinkage, making Ts<1.8. At this time, the separator actively shrinks significantly, causing the positive and negative electrodes to form a micro short circuit, thereby dissipating excess power in time, terminating continuous charging, and avoiding excessive energy accumulation that may induce chain side reactions and thermal runaway explosion. In summary, this application achieves the dual effect of ensuring the diaphragm's safety at low temperatures and its ability to actively shrink and protect at high temperatures by quantitatively matching the tensile strength and the sensitivity coefficient Ts. It eliminates the need for additional defect-inducing structures, making the design simple and controllable. It is compatible with high-capacity, high-volume energy-density energy storage cells and can effectively reduce the risk of thermal runaway and deflagration under overcharge conditions, thereby improving the overall safety of the cells and modules.

[0042] It should be noted that the calculation method of the sensitivity coefficient Ts in this application corresponds one-to-one with the test conditions: the Ts calculation formula is uniformly: Ts = (tensile strength in the MD direction + tensile strength in the TD direction) × 10 -5 / Heat shrinkage rate. Among them, the Ts value corresponding to 120℃ is calculated by substituting the heat shrinkage rate of the diaphragm measured at 120℃ and kept at a constant temperature for 1 hour (referred to as 120℃ / 1h); the Ts value corresponding to 140℃ is calculated by substituting the heat shrinkage rate of the diaphragm measured at 140℃ and kept at a constant temperature for 1 hour (referred to as 140℃ / 1h).

[0043] In a specific embodiment of this application, at 120°C, Ts is 1.8~100. For example, it can be 1.8, 2.0, 3.0, 10, 30, 50, 80, 100, or any range of the above values. Thus, by ensuring that the sensitivity coefficient Ts of the separator at 120°C is within the above range, the separator has a low thermal shrinkage rate and excellent dimensional stability at normal operating temperatures, which can stably ensure the intrinsic safety of the battery cell; at the same time, it ensures that the separator has sufficient stretching orientation and straightened chain ratio, so that sufficient thermal shrinkage can be generated at abnormally high temperatures of 140°C, achieving the protection effect of actively triggering micro-short circuits and terminating overcharge.

[0044] In a specific embodiment of this application, at 140°C, Ts is 0.1~1.7. For example, it can be 0.1, 0.3, 0.5, 0.7, 1, 1.3, 1.5, 1.7, or any range of the above values. Thus, by ensuring that the sensitivity coefficient Ts of the separator at 140°C is within the above range, the separator can generate sufficient thermal shrinkage deformation under abnormal overcharge high-temperature conditions, reliably triggering a micro-short circuit inside the cell, timely dissipating excess power, and cutting off the overcharge process; at the same time, it can avoid excessive shrinkage leading to poor dimensional stability under normal operating conditions, thus balancing the intrinsic safety of the cell and the active high-temperature protection effect.

[0045] It should be noted that this application does not specifically limit the tensile strength in the MD direction or the tensile strength in the TD direction of the diaphragm alone, as long as the sum of the tensile strengths of the two is not less than 5400 kgf / cm², and the tensile strength in at least one of the MD and TD directions is not less than 2700 kgf / cm². For example, the tensile strength in the MD direction can be taken as 2000~3500 kgf / cm²; for example, the tensile strength in the TD direction can be taken as 2000~3500 kgf / cm².

[0046] In some embodiments of this application, the thermal shrinkage rate of the separator at 120°C and after standing for 1 hour is no greater than 3%. For example, it can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 2.6%, 2.8%, 2.9%, 3%, or any range of the above values. In a preferred embodiment of this application, the thermal shrinkage rate of the separator at 120°C and after standing for 1 hour is 1% to 3%. Therefore, the calculated Ts value of the separator at a normal temperature of 120°C is ≥1.8, matching the threshold design of the sensitivity coefficient in this application, avoiding significant shrinkage deformation of the separator, ensuring the stability of the separator's geometric dimensions, reliably isolating the positive and negative electrode plates, preventing short circuits caused by direct contact between local electrode plates, and ensuring the intrinsic safety of the battery cell.

[0047] In some embodiments of this application, the thermal shrinkage rate of the separator at 140°C and after standing for 1 hour is 6% to 50%. For example, it can be 6%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or any range of the above values. In a preferred embodiment of this application, the thermal shrinkage rate of the separator at 140°C and after standing for 1 hour is 6% to 30%. Therefore, the calculated Ts value of the separator at a normal temperature of 140°C is less than 1.8, matching the threshold design of the sensitivity coefficient of this application. This allows the separator to undergo sufficient shrinkage deformation, promoting the formation of controllable micro-short circuits at the positive and negative electrodes, timely dissipating excess power, suppressing continuous charging, and preventing the continuous accumulation of energy that could induce internal chain reactions.

[0048] It should be noted that the heat shrinkage rate of the diaphragm in this application was obtained by testing using the following method: 1. Take a sample or draw a pattern with a size of 100×100mm to obtain a sample film; 2. Place the sample membrane between five A4 sheets of paper, one layer at a time, and do not stack them. 3. After the oven temperature stabilizes at the test temperature, place the prepared sample into the oven for testing; 4. Close the oven door and set the oven test time; 5. After the set time is up, remove the sample film from the oven and let it cool to room temperature. Then measure the length and width of the rectangle, record the data and calculate the heat shrinkage rate. 6. Calculation formula: Heat shrinkage rate % = (Initial mark interval length - Mark interval length after heating) / Initial mark interval length × 100%.

[0049] In some embodiments of this application, the separator includes a base membrane, at least one surface of which has an inorganic coating. This improves the overall high-temperature thermal stability of the separator, effectively constrains the relaxation of the base membrane molecular chains under medium- and high-temperature environments, suppresses thermal shrinkage deformation of the separator under normal operating conditions at 120°C, and ensures the intrinsic safety of the battery cell. Simultaneously, the inorganic coating can moderately restrain the shrinkage of the base membrane, preventing unconstrained excessive shrinkage, and ensuring that the thermal shrinkage rate of the separator is stably maintained within the range of 6% to 50% under abnormally high temperatures of 140°C. This provides sufficient deformation to trigger a controllable micro-short circuit and achieve active overcharge protection, while also preventing excessive shrinkage from causing electrode misalignment and structural damage.

[0050] In some embodiments of this application, the tensile strength of the diaphragm is related to the diaphragm thickness, which is based on the thickness of the base film.

[0051] In some embodiments of this application, the base film is a polyolefin film. In specific embodiments of this application, the base film is selected from any one of polypropylene (PP) film, polyethylene (PE) film, or a composite film of polypropylene and polyethylene. Therefore, polyolefins have high mechanical strength and good toughness, and are easily subjected to high-strength orientation control in the MD and TD directions through biaxial stretching, facilitating the formation of a high-proportion straight-chain crystalline structure, and meeting the design requirements for differentiated heat shrinkage at high and low temperatures and the Ts coefficient.

[0052] It is understood that this application does not specifically limit the thickness and porosity of the base film. Those skilled in the art can conventionally select the appropriate specifications according to the actual application conditions and cell performance requirements, as long as the tensile strength and sensitivity coefficient Ts requirements of this application are met and the overall performance of the separator and cell is not affected. For example, the thickness of the base film can be selected as 5 μm or more, such as 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, etc.; the porosity of the base film can be controlled between 35% and 45%, such as 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, etc.

[0053] In some embodiments of this application, the inorganic coating is prepared using ceramic materials. In specific embodiments of this application, the inorganic coating material is selected as alumina or boehmite. Alumina and boehmite are resistant to high temperatures and have excellent thermal stability, which can effectively constrain the thermal shrinkage deformation of polyolefin-based films, meeting the performance requirements of low shrinkage at 120°C and controllable shrinkage at 140°C for the diaphragm.

[0054] It is understood that this application does not limit the specific thickness of the inorganic coating. Those skilled in the art can make a conventional and reasonable selection based on the actual application conditions and cell performance requirements, as long as it meets the design requirements of this application for the tensile strength and sensitivity coefficient Ts of the separator, and does not affect the overall performance of the separator and the cell. For example, the thickness of the inorganic coating can be set to 4 μm or less, such as 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, or 4 μm.

[0055] In some embodiments of this application, an adhesive is provided on the surface of the inorganic coating. This allows the separator and the electrode to adhere tightly, ensuring that the overhang between the positive and negative electrodes and the separator remains constant during the manufacturing process. It also prevents deterioration of the interface contact between the positive and negative electrodes and the separator during long-term cycling, which could affect the cycle life of the battery cell. In some embodiments of this application, the adhesive is selected from polyvinylidene fluoride (PVDF).

[0056] In a second aspect, this application proposes a battery cell. According to an embodiment of this application, the battery cell includes one or more electrode cores, at least one of which includes the separator described in the first aspect. Because this battery cell uses the aforementioned separator with a specific temperature sensitivity coefficient Ts, it possesses all the structural features and technical advantages corresponding to that separator, effectively suppressing the spread of internal chain side reactions and significantly reducing the probability of overcharging, thermal runaway, and deflagration in high-capacity, high-volume-energy-density battery cells. Those skilled in the art will understand that this battery cell possesses all the advantages of the aforementioned separator, which will not be elaborated upon here.

[0057] In some embodiments of this application, the inventors conducted systematic experimental research on bipolar core structure batteries. Experimental results show that using the diaphragm with a specific temperature sensitivity coefficient Ts as described in this application for at least one bipolar core can effectively reduce the risk of core combustion and explosion. Further experiments revealed that setting differentiated Ts values ​​for the bipolar cores at 140°C, and widening the Ts difference between the two cores at 140°C, can significantly stagger the thermal runaway trigger times of the two cores; the cell's gas production rhythm and exhaust process are significantly optimized, effectively avoiding the problem of concentrated instantaneous energy release and greatly suppressing the occurrence of safety accidents such as cell combustion and explosion.

[0058] In some embodiments of this application, the cell capacity is set to be no greater than 600Ah and the volumetric energy density is no greater than 400Wh / L. Through extensive research, the inventors discovered that for conventional cells with a capacity ≤600Ah and a volumetric energy density ≤400Wh / L, limiting the separator sensitivity coefficient to meet the following conditions—Ts ≥ 1.8 at 120℃ and Ts < 1.8 at 140℃—suffices to balance the cell's normal operating stability with thermal runaway protection. However, when the cell capacity >600Ah and the volumetric energy density >400Wh / L, with the increase in cell capacity and volumetric energy density, the internal energy storage is higher, the thermal runaway energy release is greater, and the heat and gas generation rate is faster. In this case, it is necessary to further reduce the Ts value of the separator at 140℃; that is, the larger the cell capacity and the higher the volumetric energy density, the smaller the Ts value corresponding to 140℃ should be. The reason is that high-capacity, high-energy-density battery cells have a large load of active materials inside. Once abnormal conditions such as overheating or overcharging occur, heat accumulates faster, and chain side reactions and gas production and energy release are more intense. By reducing the Ts value at 140℃, the diaphragm can undergo greater thermal contraction deformation at 140℃, triggering the internal controllable micro-short circuit earlier and more sensitively. This dissipates excess energy in advance, delays the spread of thermal runaway, and buffers the instantaneous heat and gas production pressure, thereby adapting to the stringent safety design requirements of high-capacity, high-energy-density battery cells and effectively reducing the risk of combustion and explosion.

[0059] In some embodiments of this application, the specific molding structure of the electrode core is not specifically limited. Those skilled in the art can flexibly select a suitable electrode core structure based on the cell capacity, size specifications, and application scenario requirements. As long as the electrode core used can meet the core requirement of this application to achieve thermal runaway peak-shifting protection through differentiated diaphragm design, it falls within the protection scope of this application. For example, the electrode core can adopt a stacked structure, a wound structure, or other conventional molding structures in the prior art. Specifically, a stacked electrode core is formed by alternately stacking the diaphragm and cut positive and negative electrode sheets in sequence to form a stacked integral electrode core; the structure is well-organized, has low internal stress, and a uniform heat dissipation path, suitable for large-capacity, square cell designs. A wound electrode core is formed by continuously isolating and bonding the positive and negative electrode sheets with the diaphragm, then winding them together along the central axis to form a cylindrical or flat rolled electrode core; the process is mature, production efficiency is high, and the structure is compact, suitable for mass production of cylindrical cells and conventional square cells.

[0060] In some embodiments of this application, each electrode core further includes a positive electrode plate, a negative electrode plate, and an electrolyte.

[0061] In some embodiments of this application, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector, the positive active material layer including a positive active material. The specific type of positive active material is not particularly limited; as some specific embodiments, the positive active material includes at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium cobalt phosphate, lithium manganese phosphate, lithium nickel phosphate, lithium manganese oxide, binary materials, and ternary materials.

[0062] In some embodiments of this application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).

[0063] In some embodiments of this application, the positive electrode active material layer may optionally include a positive electrode conductive agent. As an example, the positive electrode conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0064] In some embodiments of this application, the positive electrode active material layer may optionally include a positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyethylene ether, polymethyl methacrylate (PMMA), polyhexamethylene propylene, and styrene-butadiene rubber (SBR).

[0065] In some embodiments of this application, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet (e.g., positive electrode active material, positive electrode conductive agent, positive electrode binder) in an organic solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0066] In embodiments of this application, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.

[0067] In some embodiments of this application, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).

[0068] In some embodiments of this application, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, etc. Silicon-based materials may include at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include at least one of elemental tin, tin oxide compounds, and tin alloys.

[0069] In some embodiments of this application, the negative electrode active material layer may optionally include a negative electrode binder. The negative electrode binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0070] In some embodiments of this application, the negative electrode active material layer may optionally include a negative electrode conductive agent. The negative electrode conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0071] In some embodiments of this application, the negative electrode active material layer may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0072] In some embodiments of this application, the negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet (e.g., negative electrode active material, negative electrode conductive agent, negative electrode binder and any other components) in an organic solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0073] In some embodiments of this application, the electrolyte may include an electrolyte salt and a solvent.

[0074] In some embodiments of this application, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).

[0075] In some embodiments of this application, the solvent may include one or more of ethylene carbonate (EC), propylene carbonate (PC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).

[0076] In a third aspect, this application proposes a battery. According to an embodiment of this application, the battery includes the cell described in the second aspect. Because the battery of this application uses an energy storage cell equipped with a temperature-sensitive separator, the cell can actively and controllably shrink during abnormal overcharging, prematurely triggering a micro-short circuit to terminate charging, suppressing the spread of thermal runaway from a single cell, and reducing the risk of cascading thermal runaway and explosion of the entire string or battery pack from the source, significantly improving the overall safety redundancy of the battery system. Those skilled in the art will understand that this battery possesses all the advantages of the aforementioned separator and cell, which will not be elaborated upon here.

[0077] In some embodiments of this application, the battery may include the form of a battery cell, a battery module, and a battery pack. In some embodiments, battery cells may be assembled into a battery module, and the number of battery cells contained in a battery module may be one or more, the specific number of which can be selected by those skilled in the art based on the application and capacity of the battery module. In some embodiments, battery modules may also be assembled into a battery pack, and the number of battery modules contained in a battery pack may be one or more, the specific number of which can be selected by those skilled in the art based on the application and capacity of the battery pack.

[0078] In a fourth aspect, this application proposes an energy storage device or system. According to embodiments of this application, the energy storage device or system includes the battery described in the third aspect. Therefore, the energy storage device or system of this application, equipped with a battery using the cells of this application, can significantly reduce the risk of cascading thermal runaway, fire, and explosion in the energy storage device, battery cluster, and even the entire energy storage system, thereby improving the overall system operational safety. Those skilled in the art will understand that this energy storage device or system possesses all the structural features and technical advantages of the aforementioned separator, cell, and battery, which will not be elaborated upon here.

[0079] The following will explain the solution of this application with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0080] Example 1 The specific fabrication process for a single-pole battery cell with a capacity of 600 Ah and a volumetric energy density of 400 Wh / L is as follows: 1. Positive electrode preparation process: Lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride were added to a mixing tank in a mass ratio of 97:1.5:1.5. Then, NMP solvent was added to prepare a positive electrode slurry with a solid content of 70% to 75%. The positive electrode slurry was then coated onto the front and back surfaces of the positive electrode current collector aluminum foil (12 μm thick) using a coating machine. After drying and rolling, a double-sided positive electrode sheet was obtained.

[0081] 2. Negative electrode preparation process: The negative electrode active materials graphite, styrene-diene rubber (SBR), sodium carboxymethyl cellulose, and conductive carbon black were added to a mixing tank in a mass ratio of 94:3:2:1. Then, deionized water was added to prepare a negative electrode slurry. The slurry with a solid content of 40% to 45% was stirred. The negative electrode slurry was then coated onto a copper foil (10 μm thick) of the negative electrode current collector using an extrusion coating machine. After drying and rolling, the negative electrode sheet was obtained.

[0082] 3. Separator: A 7μm thick PE base membrane with a porosity of 40% is selected. A 2μm alumina ceramic coating is coated on one side of the base membrane, and a PVDF (polyvinylidene fluoride) adhesive layer is sprayed on both the base membrane surface and the ceramic coating surface.

[0083] The membrane parameters are: MD+TD tensile strength: 6000 kgf / cm² 2 Sensitivity coefficient Ts at 120℃: 4.00; Sensitivity coefficient Ts at 140℃: 0.30; Heat shrinkage rate at 120℃ / 1h: 1.5%; Heat shrinkage rate at 140℃ / 1h: 20%.

[0084] 4. Electrolyte: The concentration of lithium salt LiPF6 is 1.0 mol / L. The solvent used is ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a ratio of EC:EMC:DMC=2:5:3. Additives: VC (ethyleneene carbonate) is added at 1.0%, FEC (fluoroethylene carbonate) at 2.0%, and DTD (ethylene sulfate) at 1.5%.

[0085] 5. Single-core battery cell: The positive electrode, separator, and negative electrode obtained above are stacked in a predetermined order, with the separator positioned between the corresponding positive and negative electrode to form the core. The core is then installed in a square aluminum shell, positioned and fixed, and then subjected to processes such as baking, liquid injection, and hot pressing to obtain a single-core battery cell.

[0086] Example 2 The single-cell battery was prepared using the method described in Example 1, with the difference being that the separator parameters were: MD+TD tensile strength: 5600 kgf / cm². 2Sensitivity coefficient Ts at 120℃: 4.70; Sensitivity coefficient Ts at 140℃: 0.40; Heat shrinkage rate at 120℃ / 1h: 1.2%; Heat shrinkage rate at 140℃ / 1h: 15%.

[0087] Example 3 The single-cell battery was prepared using the method described in Example 1, with the difference being that the separator parameters were: MD+TD tensile strength: 5400 kgf / cm². 2 Sensitivity coefficient Ts at 120℃: 5.4; Sensitivity coefficient Ts at 140℃: 0.9; Heat shrinkage rate at 120℃ / 1h: 1.0%; Heat shrinkage rate at 140℃ / 1h: 6%.

[0088] Example 4 The single-cell battery was prepared using the method of Example 1, with the difference being that: a 5μm thick PE base film with a porosity of 35% was used as the separator, a 2μm alumina ceramic coating was coated on one side of the base film, and a PVDF adhesive layer was sprayed on the base film surface and the ceramic coating surface, respectively.

[0089] The diaphragm parameters are: MD+TD tensile strength: 10000 kgf / cm² 2 Sensitivity coefficient Ts at 120℃: 3.33; Sensitivity coefficient Ts at 140℃: 0.20; Heat shrinkage rate at 120℃ / 1h: 3%; Heat shrinkage rate at 140℃ / 1h: 50%.

[0090] Example 5 The single-cell battery was prepared using the method of Example 1, with the difference being that: a 9μm thick PE base film with a porosity of 45% was used as the separator, a 2μm alumina ceramic coating was coated on one side of the base film, and a PVDF adhesive layer was sprayed on the base film surface and the ceramic coating surface, respectively.

[0091] The membrane parameters are: MD+TD tensile strength: 5400 kgf / cm² 2 Sensitivity coefficient Ts at 120℃: 1.80; Sensitivity coefficient Ts at 140℃: 0.11; Heat shrinkage rate at 120℃ / 1h: 3%; Heat shrinkage rate at 140℃ / 1h: 50%.

[0092] Example 6 The single-cell battery was prepared using the method of Example 1, with the difference being that: a 5μm thick PE base film with a porosity of 35% was used for the separator, a 2μm alumina ceramic coating was coated on both sides of the base film, and a PVDF adhesive layer was sprayed on both sides of the separator.

[0093] The diaphragm parameters are: MD+TD tensile strength: 10000 kgf / cm² 2Sensitivity coefficient Ts at 120℃: 50.00; Sensitivity coefficient Ts at 140℃: 1.70; Heat shrinkage rate at 120℃ / 1h: 0.2%; Heat shrinkage rate at 140℃ / 1h: 6%.

[0094] Example 7 The single-cell battery was prepared using the method described in Example 1, with the difference being that the separator parameters were: MD+TD tensile strength: 7000 kgf / cm². 2 Sensitivity coefficient Ts at 120℃: 2.50; Sensitivity coefficient Ts at 140℃: 0.20; Heat shrinkage rate at 120℃ / 1h: 2.8%; Heat shrinkage rate at 140℃ / 1h: 35%.

[0095] Example 8 The single-cell battery was prepared using the method of Example 1, with the difference being that: a 5μm thick PE base film with a porosity of 35% was used as the separator, a 2μm alumina ceramic coating was coated on one side of the base film, and a PVDF adhesive layer was sprayed on the base film surface and the ceramic coating surface, respectively.

[0096] The membrane parameters are: MD+TD tensile strength: 9800 kgf / cm² 2 Sensitivity coefficient Ts at 120℃: 9.80; Sensitivity coefficient Ts at 140℃: 1.63; Heat shrinkage rate at 120℃ / 1h: 1%; Heat shrinkage rate at 140℃ / 1h: 6%.

[0097] Example 9 The single-cell battery was prepared using the method of Example 1, with the difference being that the separator was a 9μm thick PE base film with a porosity of 45%, and a boehm ceramic coating with a total thickness of 3μm was applied to both sides.

[0098] The membrane parameters are: MD+TD tensile strength: 5500 kgf / cm² 2 Sensitivity coefficient Ts at 120℃: 5.00; Sensitivity coefficient Ts at 140℃: 0.28; Heat shrinkage rate at 120℃ / 1h: 1.1%; Heat shrinkage rate at 140℃ / 1h: 20%.

[0099] Example 10 The single-cell battery was prepared using the method described in Example 1, with the difference being that the separator parameters were: MD+TD tensile strength: 10000 kgf / cm². 2 Sensitivity coefficient Ts at 120℃: 100; Sensitivity coefficient Ts at 140℃: 0.29; Heat shrinkage rate at 120℃ / 1h: 0.1%; Heat shrinkage rate at 140℃ / 1h: 35%.

[0100] Example 11 Preparation in this embodiment Figure 3The battery cell, which employs a bipolar core AB stacked structure, has a capacity of 600Ah and a volumetric energy density of 400Wh / L. The specific fabrication process is as follows: 1. Positive electrode preparation process: Lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride were added to a mixing tank in a mass ratio of 97:1.5:1.5. Then, NMP solvent was added to prepare a positive electrode slurry with a solid content of 70% to 75%. The positive electrode slurry was then coated onto the front and back surfaces of the positive electrode current collector aluminum foil (12 μm thick) using a coating machine. After drying and rolling, a double-sided positive electrode sheet was obtained.

[0101] 2. Negative electrode preparation process: The negative electrode active materials graphite, styrene-diene rubber (SBR), sodium carboxymethyl cellulose, and conductive carbon black were added to a mixing tank in a mass ratio of 94:3:2:1. Then, deionized water was added to prepare a negative electrode slurry. The slurry with a solid content of 40% to 45% was stirred. The negative electrode slurry was then coated onto a copper foil (10 μm thick) of the negative electrode current collector using an extrusion coating machine. After drying and rolling, the negative electrode sheet was obtained.

[0102] 3. Diaphragm: The A-core uses a diaphragm: a) a 7μm thick PE base membrane with a porosity of 40%, coated with a 2μm alumina ceramic coating on one side of the base membrane, and then sprayed with PVDF adhesive layers on both the base membrane surface and the ceramic coating surface. The diaphragm parameters are: MD+TD tensile strength of 6000 kgf / cm². 2 Sensitivity coefficient Ts at 120℃: 5.00; Sensitivity coefficient Ts at 140℃: 0.28; Heat shrinkage rate at 120℃ / 1h: 1.2%; Heat shrinkage rate at 140℃ / 1h: 21%; The B electrode core uses a diaphragm b: the same structure as the diaphragm in the A electrode core. However, the diaphragm parameters are different: MD+TD tensile strength is 5000 kgf / cm²; sensitivity coefficient Ts at 120℃: 5.00; sensitivity coefficient Ts at 140℃: 2.8; heat shrinkage rate at 120℃ / 1h: 1.1%; heat shrinkage rate at 140℃ / 1h: 1.8%.

[0103] 4. Electrolyte: The concentration of lithium salt LiPF6 is 1.0 mol / L. The solvent used is ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a ratio of EC:EMC:DMC=2:5:3. Additives: VC (ethyleneene carbonate) is added at 1.0%, FEC (fluoroethylene carbonate) at 2.0%, and DTD (ethylene sulfate) at 1.5%.

[0104] 5. Bipolar Core Cell: The positive electrode, separator, and negative electrode obtained above are stacked in a predetermined order, with the separator positioned between the corresponding positive and negative electrode to form the core. The two cores are then installed into a square aluminum shell, positioned and fixed, and then subjected to processes such as baking, liquid injection, and hot pressing to obtain the bipolar core cell.

[0105] Example 12 The bipolar core AB stacked cell was prepared using the method of Example 11, with the difference being: Both the A and B electrode cores utilize a diaphragm: a) a 7μm thick PE base membrane with a porosity of 40%, coated with a 2μm alumina ceramic coating on one side of the base membrane, and then sprayed with PVDF adhesive layers on both the base membrane and the ceramic coating surface. The diaphragm parameters are: MD+TD tensile strength of 6000 kgf / cm². 2 Sensitivity coefficient Ts at 120℃: 5.00; Sensitivity coefficient Ts at 140℃: 0.28; Heat shrinkage rate at 120℃ / 1h: 1.2%; Heat shrinkage rate at 140℃ / 1h: 21%.

[0106] Comparative Example 1 The single-cell battery was prepared using the method described in Example 1, with the difference being that the separator parameters were: MD+TD tensile strength: 4000 kgf / cm². 2 Sensitivity coefficient Ts at 120℃: 3.33; Sensitivity coefficient Ts at 140℃: 1.00; Heat shrinkage rate at 120℃ / 1h: 1.2%; Heat shrinkage rate at 140℃ / 1h: 5%.

[0107] Comparative Example 2 The single-cell battery was prepared using the method described in Example 1, with the difference being that the separator parameters were: MD+TD tensile strength: 5600 kgf / cm². 2 Sensitivity coefficient Ts at 120℃: 1.6; Sensitivity coefficient Ts at 140℃: 0.16; Heat shrinkage rate at 120℃ / 1h: 3.5%; Heat shrinkage rate at 140℃ / 1h: 35%.

[0108] Comparative Example 3 The single-cell battery was prepared using the method of Example 9, with the difference being that the separator was a 9μm thick PE base film with a porosity of 45%, and a boehm ceramic coating with a total thickness of 3μm was applied to both sides.

[0109] The diaphragm parameters are: MD+TD tensile strength: 3600 kgf / cm² 2 Sensitivity coefficient Ts at 120℃: 5.00; Sensitivity coefficient Ts at 140℃: 2.80; Heat shrinkage rate at 120℃ / 1h: 1.1%; Heat shrinkage rate at 140℃ / 1h: 4%.

[0110] Comparative Example 4 The bipolar core AB stacked cell was prepared using the method of Example 11, with the difference being: Both electrode cores A and B employ a diaphragm b: a 7μm thick PE base membrane with a porosity of 40%, coated with a 2μm alumina ceramic coating on one side of the base membrane, and a PVDF adhesive layer sprayed onto both the base membrane and the ceramic coating surface. The diaphragm parameters are as follows: MD+TD tensile strength: 5000 kgf / cm²; sensitivity coefficient Ts at 120℃: 5.00; sensitivity coefficient Ts at 140℃: 2.8; thermal shrinkage rate at 120℃ / 1h: 1.1%; thermal shrinkage rate at 140℃ / 1h: 1.8%.

[0111] [Performance Testing] I. Testing Methods 1. Hot box pass rate test: The battery cells of Examples 1-12 and Comparative Examples 1-4 were fully charged (3.2V) and placed in an oven at 1300°C for 30 minutes; No fire or explosion shall occur during or after the test; The percentage of batteries that do not catch fire or explode is statistically analyzed.

[0112] 2. Explosion / ignition rate test: The battery cells of Examples 1-12 and Comparative Examples 1-4 were fully charged and tested. Temperature sensors were installed on the large surface of the battery cells before the test. The battery cell equipped with the sensor was placed between two 1500W heating plates for constant power heating and constant current charging at 0.5C. When the temperature rise rate of the large-area sensor is >1℃ / s, the time is recorded for three consecutive seconds; this is the time of loss of control. The total energy charged during this period is the charged energy. If a battery explodes or catches fire, it is recorded as a deflagration, and the deflagration rate is the number of deflagrations divided by the total number of batteries.

[0113] II. Test Results 1. The shrinkage results of the diaphragms in Example 1 and Comparative Example 1 at 140°C / 1h are as follows: Figure 1 As shown. The thermal shrinkage rate of the diaphragm in this application is 20%, while the thermal shrinkage rate of the comparative diaphragm is only 5%. Compared to the comparative diaphragm, the diaphragm in this application exhibits a more significant thermal shrinkage deformation capability at a high temperature of 140°C. Figure 2 The test results show that the battery cell with separator 1 has a significantly lower cumulative energy charge, indicating that it can safely release energy in a smaller energy accumulation stage, greatly reducing the severity of thermal runaway and demonstrating better battery cell safety performance.

[0114] 2. The test results of the single-cell battery are shown in Table 1. Through the comparative tests of Examples 1-10 and Comparative Examples 1-3, it can be seen that the present application uses a specific temperature-sensitive diaphragm, which can achieve the dual functions of low temperature low shrinkage and high temperature active shrinkage failure. While ensuring the intrinsic safety of the battery cell, it can actively trigger the internal short circuit of the battery cell, terminate abnormal charging in advance, reduce energy accumulation, and reduce the risk of battery cell explosion.

[0115] Table 1

[0116] 3. The test results of the multi-core cells are shown in Table 2. Comparative tests of Examples 11-12 and Comparative Example 4 show that the AB stacked core differentiated diaphragm design can further extend the thermal runaway time of different cores, optimize the gas generation and exhaust processes, and reduce the cell deflagration rate to 0%. Experimental results demonstrate that this application, through the combination of diaphragm temperature sensitivity and multi-core structure, can effectively solve the technical problem of thermal runaway caused by overcharging in large-capacity, high-volume-energy-density energy storage cells, significantly improving safety performance.

[0117] Table 2

[0118] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.

Claims

1. A diaphragm, characterized in that, The sensitivity coefficient Ts of the diaphragm satisfies: At 120℃, Ts≥1.8; At 140℃, Ts < 1.8; Where Ts = (tensile strength in the MD direction + tensile strength in the TD direction) × 10 -5 / heat shrinkage rate; The sum of the tensile strength in the MD direction and the tensile strength in the TD direction of the diaphragm is ≥5400 kgf / cm². 2 .

2. The diaphragm according to claim 1, characterized in that, The diaphragm satisfies at least one of the following conditions: The thermal shrinkage rate of the diaphragm under the condition of standing at 120°C for 1 hour is no greater than 3%; The thermal shrinkage rate of the diaphragm under the condition of standing at 140°C for 1 hour is 6%~50%; At 120℃, Ts is 1.8~100; At 140℃, Ts is 0.1~1.

7.

3. The diaphragm according to claim 2, characterized in that, The thermal shrinkage rate of the diaphragm under the condition of standing at 120°C for 1 hour is 1%~3%; And / or, the thermal shrinkage rate of the diaphragm under the condition of standing at 140°C for 1 hour is 6%~30%.

4. The diaphragm according to claim 3, characterized in that, The diaphragm includes a base membrane, and at least one surface of the base membrane has an inorganic coating.

5. The diaphragm according to claim 4, characterized in that, The tensile strength of the diaphragm is related to the thickness of the diaphragm, which is based on the thickness of the base film. And / or, the base film is selected from polyolefin films; the polyolefin film is selected from any one of polypropylene films, polyethylene films, or composite films of polypropylene and polyethylene; And / or, the thickness of the base film is ≥3μm; And / or, the porosity of the base membrane is 25% to 45%.

6. The diaphragm according to claim 4, characterized in that, The inorganic coating is made of alumina or boehmite. And / or, the thickness of the inorganic coating is ≤4μm; And / or, the surface of the inorganic coating is provided with an adhesive.

7. A battery cell, characterized in that, It includes one or more electrode cores, at least one of the electrode cores including the diaphragm according to any one of claims 1 to 6.

8. The battery cell according to claim 7, characterized in that, The battery cell includes multiple electrode cores, and the separators of at least two electrode cores have different Ts values ​​at 140°C.

9. A battery, characterized in that, Includes the battery cell described in any one of claims 7 to 8.

10. An energy storage device or energy storage system, characterized in that, Includes the battery as described in claim 9.